Working Capital Management Efficiency using the Index Method - Rahman, Abdul (Journal of Economics and Management, 2023)
In order to better understand working capital management, which includes efficient handling of current assets as well as current liabilities? Efficient management of working capital is a precondition for the success of any kind of firm. The initial study's major goal was to assess the efficiency of working capital management in the automobile industry. The present study deals with the efficiency of working capital management in the selected four-wheeler passenger car manufacturing companies in India. The source of secondary data is the annual report and CMIE Prowess. The database of ten passenger car manufacturing companies in India is drawn at random from the source Statista based on their market share and brand in terms of passenger car manufacturing companies for the 10-year period from 2011–12 to 2020–21. This study employed three parameters to assess the efficiency of working capital management: the performance index of working capital management (PI), the utilization index of working capital management (UI), and the efficiency index of working capital management (EI). following the model suggested by Bhattacharya (1997). This study's results show most of the companies reviewed did well in terms of working capital performance, current asset usage, and working capital efficiency. Some selected passenger car manufacturers have efficiently managed their working capital and increased sales with existing assets. Companies with a low or negative efficiency index must use current assets efficiently to manage working capital. We feel this is an important topic that would be of interest in decision-making. Company managers in managing the company's finances must be more effective and efficient so that the company does not experience financial distress. For investors, it can be used as a reference in making decisions to invest by looking at companies that show companies that have good financial performance.